DESIGN OF FINISHED GOODS INSPECTION ACCELERATION WITH QCC METHOD AND SEVEN TOOLS TO INCREASE PRODUCTIVITY - Aprina, Budi; Ruspendi, Ruspendi (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2021)
The manufacturing industry in the current era of globalization is very strict. Speed to produce products is important now, not only in terms of process. Developing a new product at PT. Surya Toto Indonesia has been running well, only in the process there are still found the exceeded of time or schedule of work plans that have been made. The preparation process for carrying out this test will take more time. Because the test aids have not been prepared or have not been grouped according to the type of finished goods or according to the series. It is necessary to analyze using the seven tool method and assisted by factor analysis to find the dominant cause and corrective action. It was found the old problem in the inspection process was the dress-up process or preparation for the test. Because the test kits are incomplete and not permanent, also the test kits do not have a storage area and lack of employee’s ability to process them. Employee education, complete equipment components, and also need to make permanent test kits and according to the specifications of finished goods. Storage area for the test kits so that it is not scattered and messy.